Neutrophil extracellular traps cause airway obstruction during respiratory syncytial virus disease. Issue 3 (21st December 2015) - Cortjens, Bart; de Boer, Onno J; de Jong, Rineke; Antonis, Adriaan FG; Sabogal Piñeros, Yanaika S; Lutter, René; van Woensel, Job BM; Bem, Reinout A
Abstract: Human respiratory syncytial virus (RSV) is the most important cause of severe lower respiratory tract disease (LRTD) in young children worldwide. Extensive neutrophil accumulation in the lungs and occlusion of small airways by DNA‐rich mucus plugs are characteristic features of severe RSV–LRTD. Activated neutrophils can release neutrophil extracellular traps (NETs), extracellular networks of DNA covered with antimicrobial proteins, as part of the first‐line defence against pathogens. NETs can trap and eliminate microbes; however, abundant NET formation may also contribute to airway occlusion. In this study, we investigated whether NETs are induced by RSV and explored their potential anti‐viral effect in vitro . Second, we studied NET formation in vivo during severe RSV–LRTD in infants and bovine RSV–LRTD in calves, by examining bronchoalveolar lavage fluid and lung tissue sections, respectively. NETs were visualized in lung cytology and tissue samples by DNA and immunostaining, using antibodies against citrullinated histone H3, elastase and myeloperoxidase. RSV was able to induce NET formation by human neutrophils in vitro . Furthermore, NETs were able to capture RSV, thereby precluding binding of viral particles to target cells and preventing infection. Evidence for the formation of NETs in the airways and lungs was confirmed in children with severe RSV–LRTD. Detailed histopathological examination of calves with RSV–LRTD showed extensive NET formation in dense plugs occluding the airways, either with or without captured viral antigen. Together, these results suggest that, although NETs trap viral particles, their exaggerated formation during severe RSV–LRTD contributes to airway obstruction. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.